Extraction of Polyethylene and Polypropylene Microplastic from Agriculture Soil - V. V. Dhoble,; L. B. Dama, (International Journal of Scientific Research in Science and Technology, 2024)
The rapid population growth worldwide is intensifying the pressure on the agricultural sector. Concurrently, significant climate changes and the increasing load of soil pollutants are creating formidable challenges for agroecosystems, adversely affecting crop productivity and quality. Microplastics are among the most pervasive pollutants, having already infiltrated all terrestrial and aquatic environments. The rising concentration of microplastics in soil significantly impacts crop plant growth and yield. This study elaborates on the presence of microplastics in soil and their effects on soil quality and plant growth. It demonstrates that microplastics alter the soil's biophysical properties, such as water-holding capacity, bulk density, aeration, texture, and microbial composition. Furthermore, microplastics interact with various pollutants, including polyaromatic hydrocarbons and heavy metals, increasing their bioavailability to crops. The study also provides detailed insights into current techniques for the isolation and identification of soil microplastics, addressing key challenges and highlighting research gaps. This comprehensive analysis and comparison of interconnected aspects aim to provide a deeper understanding of all research perspectives on microplastics in agroecosystems.
Keywords: Agriculture Soil; Microplastic; Hydrocarbon; Polyethylene; Extraction